Feasibility and Acceptability of Community Coronavirus Disease 2019 Testing Strategies (FACTS) in a University Setting. (4th October 2021) - Hirst, Jennifer A; Logan, Mary; Fanshawe, Thomas R; Mwandigha, Lazaro; Wanat, Marta; Vicary, Charles; Perera, Rafael; Tonkin-Crine, Sarah; Lee, Joseph Jonathan; Tracey, Irene; Duff, Gordon; Tufano, Peter; et al.
Abstract: Background: During the coronavirus disease 2019 (COVID-19) pandemic in 2020, the UK government began a mass severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing program. This study aimed to determine the feasibility and acceptability of organized regular self-testing for SARS-CoV-2. Methods: This was a mixed-methods observational cohort study in asymptomatic students and staff at University of Oxford, who performed SARS-CoV-2 antigen lateral flow self-testing. Data on uptake and adherence, acceptability, and test interpretation were collected via a smartphone app, an online survey, and qualitative interviews. Results: Across 3 main sites, 551 participants (25% of those invited) performed 2728 tests during a follow-up of 5.6 weeks; 447 participants (81%) completed at least 2 tests, and 340 (62%) completed at least 4. The survey, completed by 214 participants (39%), found that 98% of people were confident to self-test and believed self-testing to be beneficial. Acceptability of self-testing was high, with 91% of ratings being acceptable or very acceptable. A total of 2711 (99.4%) test results were negative, 9 were positive, and 8 were inconclusive. Results from 18 qualitative interviews with students and staff revealed that participants valued regular testing, but there were concerns about test accuracy that impacted uptake and adherence. Conclusions: This is the first study to assess feasibility and acceptability of regular SARS-CoV-2 self-testing. It provides evidence to inform recruitment for, adherence to, and acceptability of regular SARS-CoV-2 self-testing programs for asymptomatic individuals using lateral flow tests. We found that self-testing is acceptable and people were able to interpret results accurately.